Multidrug Resistant Salmonella Spp. and Staphylococcus Spp. Isolated from milk in Dhaka City - Allied, Md. Anamul Hasan (Brac University, 2022)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2021.